2022
DOI: 10.1093/gbe/evac122
|View full text |Cite
|
Sign up to set email alerts
|

A Chromosome-Length Reference Genome for the Endangered Pacific Pocket Mouse Reveals Recent Inbreeding in a Historically Large Population

Abstract: High-quality reference genomes are fundamental tools for understanding population history, and can provide estimates of genetic and demographic parameters relevant to the conservation of biodiversity. The federally endangered Pacific pocket mouse (PPM), which persists in three small, isolated populations in southern California, is a promising model for studying how demographic history shapes genetic diversity, and how diversity in turn may influence extinction risk. To facilitate these studies in PPM, we combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…However, the shorter-than-expected distribution of RoH in reintroduced individuals, given the known timing of the reintroduction founder effects, suggests our analysis underestimated RoH lengths, and this is consistent with an excess of short (<50-Kbp) gaps between RoH in our data, breaking up otherwize long RoH (Figure S9). RoH after allowing one <50-Kbp gap within each 1-Mbp segment (similar to Wilder et al, 2022) gave qualitatively similar results but showed more long RoH which aligned more closely with the known timing of the reintroduction founder events (Figure S10).…”
Section: Effect Of Reintroduction Versus Recolonization On Genome-wid...supporting
confidence: 63%
“…However, the shorter-than-expected distribution of RoH in reintroduced individuals, given the known timing of the reintroduction founder effects, suggests our analysis underestimated RoH lengths, and this is consistent with an excess of short (<50-Kbp) gaps between RoH in our data, breaking up otherwize long RoH (Figure S9). RoH after allowing one <50-Kbp gap within each 1-Mbp segment (similar to Wilder et al, 2022) gave qualitatively similar results but showed more long RoH which aligned more closely with the known timing of the reintroduction founder events (Figure S10).…”
Section: Effect Of Reintroduction Versus Recolonization On Genome-wid...supporting
confidence: 63%
“…The range of ROH in hammerhead extended up to over 3 Mbp, shorter than those arising from very recent inbreeding in some other wildlife (e.g. Soay sheep 34 and endangered Pacific pocket mice 35 ), aquaculture species like coho salmon, 36 and in animal livestock. 37 Our calculations suggest the longest ROH in hammerhead stem from inbreeding within possibly the last ∼60–200 years, assuming a generation time of 25 years and a recombination rate of 6.5 cM/Mb.…”
Section: Discussionmentioning
confidence: 97%
“…2018), thus lacking a chromosome-level genome assembly, we only included scaffolds longer than 10 Mbp in RoH analyses; (3) Errors in mapping sequence reads or structural variation between the caribou reference genome assembly and the Svalbard reindeer genome could also break up long RoH. Reanalysing RoH after allowing one <50-Kbp gap within each 1-Mbp segment (similar to Wilder et al . (2022)) gave qualitatively similar results but showed more long RoH which aligned more closely with the known timing of the reintroduction bottleneck (Fig S10).…”
Section: Discussionmentioning
confidence: 99%